1994
DOI: 10.1128/mcb.14.7.4565
|View full text |Cite
|
Sign up to set email alerts
|

trans-spliceosomal U6 RNAs of Crithidia fasciculata and Leptomonas seymouri: deviation from the conserved ACAGAG sequence and potential base pairing with spliced leader RNA.

Abstract: U6 RNA genes from the trypanosomatids Crithidia fasciculata and Leptomonas seymouri have been isolated and sequenced. As in Trypanosoma brucei, the U6 RNA genes in both C.fasciculata and L. seymouri are arranged in close linkage with upstream tRNA genes. The U6 RNA sequences from C. fasciculata and L. seymouri deviate in five and three positions, respectively, from the published T. brucei sequence. Interestingly, both C.fasciculata U6 RNA genes carry a C->T change at the second position of the ACAGAG hexanucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 52 publications
2
11
0
Order By: Relevance
“…U6 snRNA gene is present in a single copy (Fig. 4, panel D), as similarly shown for T. brucei (Mottram et al 1989), L. seymouri (Xu et al 1994), L. collosoma (Goldring & Michaeli 1995), Phytomonas sp. and Leishmania mexicana (Wieland & Bindereif 1995).…”
Section: T Cruzi X H Sapiens Snrnas -A Comparison Betweensupporting
confidence: 76%
See 1 more Smart Citation
“…U6 snRNA gene is present in a single copy (Fig. 4, panel D), as similarly shown for T. brucei (Mottram et al 1989), L. seymouri (Xu et al 1994), L. collosoma (Goldring & Michaeli 1995), Phytomonas sp. and Leishmania mexicana (Wieland & Bindereif 1995).…”
Section: T Cruzi X H Sapiens Snrnas -A Comparison Betweensupporting
confidence: 76%
“…3b, indicated by boxes). The single loop of T. cruzi U5 snRNA is conserved among the other trypanosomatids, but L. collosoma (Xu et al 1994), C. fasciculata (Schnare & Gray 2000) and H. sapiens (Baserga & Steitz 1993) show an additional loop at the 3' end.…”
Section: Pcr Amplification Cloning and Sequencing Of T Cruzi U2 U4mentioning
confidence: 99%
“…Interestingly, Crithidia U6 carries a C-to-U change in the second position of the ACAGAG sequence and a compensatory base change of the corresponding SL RNA at position ϩ5 (105). These phylogenetic data also support the 5Ј splice site-U6 interaction.…”
Section: Sl-snrna Interactionssupporting
confidence: 60%
“…Because of space limitation, we chose to discuss snRNAs that have unique features in trypanosomes. Detailed information on U6 and U4 from different trypanosomatid species is not covered in this review but can be found in (8,26,44,105).…”
Section: Snrnas Involved In Trans and Cis Splicingmentioning
confidence: 99%
“…Likewise, no Ul homolog has been identified in trypanosomatids, in which all mRNAs are believed to arise via trans-splicing (for review, see Nilsen 1992). The recent analysis of a new trans-spliceosomal U6 RNA gene (Xu et al 1994) has revealed compensatory base changes within the conserved hexanucleotide sequence of U6 and the 5' splice sites of SL RNAs, suggesting that the 5' splice site-U6 snRNA interaction is universal among splicing systems. In contrast, functions attrib uted to Ul snRNA appear to be dispensable for group II intron removal and for trans-splicing.…”
Section: Functions and Evolution Of The Ul Snrnamentioning
confidence: 99%